The Development of Magic Hat Media to Improve The Children Language Aspects of 5-6 Year Old at RA Al Khairiyah - Cindy Putri Dinata; Muhammad Yusuf; Leli Fertiliana Dea; Siti Roudhotul Jannah; Ferdian Utama (Bulletin of Pedagogical Research, 2024)
The purpose of this study was to develop a magic hat media to improve the language aspect of children aged 5-6 years at RA Al Khairiyah, Melinting District, East Lampung Regency in the 2023-2024 Academic Year. This study is a research and development (R&D) study using the 4D model consisting of define, design, develop, disseminate. The subjects of this study were children aged 5-6 years at RA Al Khairiyah, Melinting District, totaling 12 children. The effectiveness of using a magic hat to improve the language aspect of children aged 5-6 years, namely after conducting research at RA Al Khairiyah, Melinting District using a magic hat, it was proven that the language aspect abilities of early childhood children could develop. Before using the magic hat, the language aspect abilities of early childhood children out of 12 children, there were 7 children who received the Not Yet Developing category, and 5 children who received the Starting to Develop category, while none were included in the category of developing according to expectations and developing very well. Then after using the magic hat, the children's language aspect abilities Developed According to Expectations. The contribution of this research includes the fact that this research can develop children's language skills and foster children's enthusiasm for learning. In addition, this research provides an alternative for selecting suitable learning media in the teaching and learning process.